A three-gene signature might predict prognosis in patients with acute myeloid leukemia. Issue 6 (3rd June 2020) - Zhu, Xin; Zhao, Qian; Su, Xiaoyu; Ke, Jinming; Yi, Yunyun; Yi, Jing; Lin, Jiang; Qian, Jun; Deng, Zhaoqun
Abstract: The identification of effective signatures is crucial to predict the prognosis of acute myeloid leukemia (AML). The investigation aimed to identify a new signature for AML prognostic prediction by using the three-gene expression (octamer-binding transcription factor 4 (OCT4), POU domain type 5 transcription factor 1B (POU5F1B) and B-cell-specific Moloney murine leukemia virus integration site-1 pseudogene 1 (BMI1P1). The expressions of genes were obtained from our previous study. Only the specimens in which three genes were all expressed were included in this research. A three-gene signature was constructed by the multivariate Cox regression analyses to divide patients into high-risk and low-risk groups. Receiver operating characteristic (ROC) analysis of the three-gene signature (area under ROC curve (AUC) = 0.901, 95% CI: 0.821–0.981, P <0.001) indicated that it was a more valuable signature for distinguishing between patients and controls than any of the three genes. Moreover, white blood cells (WBCs, P =0.004), platelets (PLTs, P =0.017), percentage of blasts in bone marrow (BM) ( P =0.011) and complete remission (CR, P =0.027) had significant differences between two groups. Furthermore, high-risk group had shorter leukemia-free survival (LFS) and overall survival (OS) than low-risk group ( P =0.026; P =0.006), and the three-gene signature was a prognostic factor. Our three-gene signature for prognosis prediction in AML may serve as a prognostic biomarker.